The role of folic acid on the hyperhomocysteinemia in the Buerger's disease (Thromboangiitis Obliterans) - Beigi, Ali Akbar (J Res Med Sci, 2014)
BACKGROUND: The mechanism underlying Buerger's disease (BD) is still unknown. Recently, thrombophilic conditions predisposing to a hypercoagulable state have been hypothesized as triggers for BD. The aim of the study is to evaluate the prevalence of the hyperhomocysteinemia and level of the anticardiolipin antibodies, and the role of folic acid on the hyperhomocysteinemia and on the rate of the amputations in the patients with BD. MATERIALS AND METHODS: In an experimental placebo-controlled double-blinded study, between 2004 and 2010, thirty patients with BD were randomly assigned into two groups (14 patients in a drug group and 16 patients in the placebo group). Drug or placebo was administered, and they were followed in 2 and 6 months for homocysteine, Anticardiolipin antibodies and the risk of amputations. RESULTS: At the beginning of the study homocysteine level was higher than normal in 19 patients (63%). There was a significant decrease in homocysteine level during 6 months in folic acid group (P < 0.001), but there was no change in the placebo group. None of our patients had elevated Anticardiolipin antibodies, and there was no change in the level of Anticardiolipin antibody during study. High level of homocysteine did not associate with more amputations during 6 months of study (P > 0.05). CONCLUSION: This study shows the hyperhomocysteinemia in BD, and the benefit of folic acid treatment in homocysteine lowering, but folic acid doesn’t inhibit the risk of major and minor amputation during 6 months of follow-up. Longer follow-up may reveal the role of folic acid in these patients